Hubungan Regulasi, Ketertiban, Kepatuhan Dan Motivasi Pegawai Terhadap Kepemimpinan Kepala Desa Di Desa Pengalangan Kecamatan Menganti Kabupaten Gresik - Mu'di, Ahmad; Supadi, Supadi; Sundioto, Sundioto (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2024)
The purpose of this study was to determine the existence of Regulation, Orderliness, Compliance and Employee Motivation to have a relationship with the Village Head Leadership in Pengalangan Village simultaneously and partially. The population in this study was 58 employees so that the sample used was the entire population or full sampling of 58 respondents. The research method used the T-test, F test, and multiple linear regression, the T-test above obtained the results of variable X1 (regulation) of 0,000 which is smaller than α of 0.05, which means that the regulatory variable has a partial relationship to leadership. Whereas X2 (Order) has a significance of 0.0000 which is smaller than α of 0.05, which means Order has a partial relationship with leadership, while the X3 Signification (Compliance) is 0.000 which is smaller than α of 0.05 which means that compliance has a partial relationship to leadership, but the significance value of X4 (employee motivation is 0.208 which is greater than α of 0.05, which means that motivation does not have a partial relationship with leadership. amounting to 4.01 which means that simultaneously regulation, order, obedience, and motivation have a simultaneous relationship to leadership.